2005
DOI: 10.1097/01.opx.0000192348.37026.09
|View full text |Cite
|
Sign up to set email alerts
|

Orbscan Global Pachymetry: Analysis of Repeated Measures

Abstract: Orbscan is capable of giving repeatable pachymetry readings that are comparable to the ultrasound pachymeter within the central and thinnest point of the cornea. There is a gradual loss of repeatability toward the peripheral cornea possibly as a result of a lack of overlapping data points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…30 The current CV w value was more consistent than scanning-slit pachymetry (Orbscan II, Bausch & Lomb), which has CV w values ranging from 0.67% to 0.80%. 27 Regarding the interobserver reproducibility with the Lenstar LS 900 device, we did not find a significant difference between the CCT data obtained by the 2 examiners and the mean difference between a set of measurements was clinically negligible (1.35 mm). However, the interobserver CV w (2.10%) was not as good as the intraobserver CV w value (0.42%).…”
Section: Discussionmentioning
confidence: 77%
“…30 The current CV w value was more consistent than scanning-slit pachymetry (Orbscan II, Bausch & Lomb), which has CV w values ranging from 0.67% to 0.80%. 27 Regarding the interobserver reproducibility with the Lenstar LS 900 device, we did not find a significant difference between the CCT data obtained by the 2 examiners and the mean difference between a set of measurements was clinically negligible (1.35 mm). However, the interobserver CV w (2.10%) was not as good as the intraobserver CV w value (0.42%).…”
Section: Discussionmentioning
confidence: 77%
“…The pachymetric values variation, observed in both patients groups, remained within the normal limits for the test (24)(25)(26) (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we have compared the central corneal edema of patients submitted to cataract surgery performed with conventional phacoemulsification in one eye and with liquefaction, by Aqualase ® , in the fellow There was no statistically significant difference between the groups considering pre and postoperative corneal thickness average, measured by pachymetry with Orbscan II ® (24) . The pachymetric values variation, observed in both patients groups, remained within the normal limits for the test (24)(25)(26) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Another well studied non-contact method for measuring CCT is the Orbscan II (Bausch & Lomb, Rochester, NY) (3,10,11,13,16,17) . Giraldez Fernandez et al (10) found that the Orbscan measurement of CCT were greater that ultrasonic pachymeter measurements, a difference that was statistically significantly.…”
Section: Discussionmentioning
confidence: 99%